Efektivitas Model Pembelajaran Game-Based Learning terhadap Hasil Belajar Peserta Didik pada Pembelajaran IPS Kelas VII SMP Negeri 6 Pontianak - Maharani Maharani; Aminuyati Aminuyati; Hadi Wiyono; Sri Buwono; Venny Karolina (Journal on Education, 2024)
The purpose of this study is to determine the effectiveness of the Game-Based Learning model on students' learning outcomes in Social Studies education at SMP Negeri 6 Pontianak. This research employs a quantitative experimental design using a Quasi-Experimental Design research design with a Nonequivalent Control Group Design. The research techniques used are direct observation and measurement techniques. Data collection instruments consist of observation sheets, learning outcome tests, and documentary sheets. The analysis technique used involves normality tests, hypothesis testing, and effect size tests. The learning outcomes in the Game-Based Learning model in the experimental class obtained an average score of 83.70, while in the control class, the average score was 63.39. This condition indicates that the Game-Based Learning model is more effective compared to conventional learning models. This is evidenced by the effect size test result of 2.1555, which is classified as high. Thus, it can be concluded that the Game-Based Learning model is effective in improving students' learning outcomes in Social Studies education for eighth-grade students at SMP Negeri 6 Pontianak.